2017
DOI: 10.1016/j.gca.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Boron isotope sensitivity to seawater pH change in a species of Neogoniolithon coralline red alga

Abstract: The increase in atmospheric carbon dioxide (CO2) observed since the industrial revolution has reduced surface ocean pH by ~0.1 pH units, with further change in the oceanic system predicted in the coming decades. Calcareous organisms can be negatively affected by extreme changes in seawater pH (pHsw) such as this due to the associated changes in the oceanic carbonate system. The boron isotopic composition (δ 11 B) of biogenic carbonates has been previously used to monitor pH at the calcification site (pHcf) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 88 publications
7
43
1
Order By: Relevance
“…For example, Cusack et al (2015) reported 30 % trigonal boron in the calcite lattice of a different species of coralline alga. Therefore, boric acid incorporation alone cannot explain the anomalously elevated δ 11 B CaCO 3 observed here for coralline algae (see also discussion in Donald et al, 2017). Moreover, although nuclear magnetic resonance spectroscopy reveals that trigonal boron is present in the calcite lattice, it cannot determine whether boric acid was incorporated directly into the calcite lattice, or if the trigonal boron originated from borate post-mineralization (e.g., see alternative mechanisms of boron incorporation discussed in Klochko, 2006;Noireaux et al, 2015).…”
Section: Coralline Red Alga (Neogoniolithon Sp)mentioning
confidence: 74%
See 1 more Smart Citation
“…For example, Cusack et al (2015) reported 30 % trigonal boron in the calcite lattice of a different species of coralline alga. Therefore, boric acid incorporation alone cannot explain the anomalously elevated δ 11 B CaCO 3 observed here for coralline algae (see also discussion in Donald et al, 2017). Moreover, although nuclear magnetic resonance spectroscopy reveals that trigonal boron is present in the calcite lattice, it cannot determine whether boric acid was incorporated directly into the calcite lattice, or if the trigonal boron originated from borate post-mineralization (e.g., see alternative mechanisms of boron incorporation discussed in Klochko, 2006;Noireaux et al, 2015).…”
Section: Coralline Red Alga (Neogoniolithon Sp)mentioning
confidence: 74%
“…Many calcifying marine organisms, including scleractinian corals (Al-Horani et al, 2003;Cohen and Holcomb, 2009;Cohen and McConnaughey, 2003;Rollion-Bard et al, 2003Holcomb et al, 2010;Krief et al, 2010;Trotter et al, 2011;Ries, 2011a;Anagnostou et al, 2012;Wall et al, 2016), coralline red algae (Borowitzka and Larkum, 1987;McConnaughey and Whelan, 1997;Donald et al, 2017), calcareous green algae (Borowitzka and Larkum, 1987;De Beer and Larkum, 2001;McConnaughey and Falk, 1991), foraminifera (Rink et al, 1998;Zeebe and Sanyal, 2002), and crabs (Cameron, 1985) …”
Section: The Role Of Calcification Site Ph In Calcareous Biomineralizmentioning
confidence: 99%
“…It marginally decreased with seawater Ω for P. damicornis . While there are no published data of B/Ca or Raman spectroscopy for abiogenic high‐Mg calcites, both have been interpreted as carbonate system proxies in CCA (Donald, Ries, Stewart, Fowell, & Foster, ; Kamenos et al., ). We interpret B/Ca and Raman spectra as indicative of calcifying fluid DIC and calcite saturation state (Ω Cal cf ) respectively (Figure ) based on their systematics in aragonite.…”
Section: Resultsmentioning
confidence: 99%
“…Seawater Ω did not influenced DIC cf in A. yongei. In the three treatments with similar Ω, DIC cf was the highest (and B/Ca the lowest for CCA) in the treatment with elevated DIC.Mg calcites, both have been interpreted as carbonate system proxies in CCA(Donald, Ries, Stewart, Fowell, & Foster, 2017;Kamenos et al, 2013). We interpret B/Ca and Raman spectra as indicative of calcifying fluid DIC and calcite saturation state (Ω Cal cf ) respectively (…”
mentioning
confidence: 82%
“…Observed non-negative effects may be the result of individual resilience or the capacity of certain species to acclimatize to OA. One way this may occur is via the maintenance of pH homeostasis at the site of calcification despite an increasingly acidic environment, which is a polyphyletic response to ocean acidification (Liu et al, 2018) that has been observed in scleractinian corals (Al-Horani et al, 2002;Ries, 2011;Venn et al, 2011;McCulloch et al, 2012;Holcomb et al, 2014) , foraminifera (Rink et al, 1998;Köhler-Rink and Kühl, 2000;de Nooijer et al, 2008de Nooijer et al, , 2009 , calcareous green algae (De Beer and Larkum, 2001) , coralline red algae (Donald et al, 2017;Anagnostou et al, 2019;Liu et al, 2020) , coccolithophores (Liu et al 2018), and bivalves (Ramesh et al, 2017;Cameron et al, 2019) . In bivalves, calcification occurs within the extrapallial fluid (EPF) located between the shell and mantle epithelium, the composition of which is regulated via the active exchange of ions and other constituents through the mantle epithelium (Crenshaw and Neff, 1969;Crenshaw, 1972) .…”
Section: Introductionmentioning
confidence: 99%